The Dates of the Philosophical Sutras of the Brahmans - Jacobi, Hermann, 1850-1937 (Analecta Gorgiana ;, 2010)
The author is concerned with finding the dates of composition of the Buddhist doctrines the Sunyavada and the Vijnanavada. It was concluded that the Vijnanavada was arranged later than the Sunyavada.